2019
DOI: 10.1016/j.stem.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Human ESC-Derived Chimeric Mouse Models of Huntington’s Disease Reveal Cell-Intrinsic Defects in Glial Progenitor Cell Differentiation

Abstract: Huntington’s disease (HD) is characterized by hypomyelination as well as neuronal loss. To assess the basis for myelin loss in HD, we generated bipotential glial progenitor cells (GPCs) from human embryonic stem cells (hESCs), derived from huntingtin (mHTT)-mutant embryos or normal controls, and performed RNAseq to assess mHTT-dependent changes in gene expression. In hGPCs derived from 3 mHTT hESC lines, transcription factors associated with glial differentiation and myelin synthesis were sharply down-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 43 publications
6
98
0
Order By: Relevance
“…ESC derived GPC In vitro/in vivo (Osipovitch et al, 2019) Schizophrenia: OPC with CSPG4 mutation present abnormal morphology, impaired viability, and defective maturation to oligodendrocytes upon culture on organotypic slices of shiverer mice. Schizophrenia: GPC exhibit disrupted expression of glial differentiation-associated genes.…”
Section: Description And/or Results Of Study Type Of Cells Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…ESC derived GPC In vitro/in vivo (Osipovitch et al, 2019) Schizophrenia: OPC with CSPG4 mutation present abnormal morphology, impaired viability, and defective maturation to oligodendrocytes upon culture on organotypic slices of shiverer mice. Schizophrenia: GPC exhibit disrupted expression of glial differentiation-associated genes.…”
Section: Description And/or Results Of Study Type Of Cells Experimentmentioning
confidence: 99%
“…Many of the neurodegenerative diseases display MRI or histological abnormalities in white matter, but it has been assumed that these imaging abnormalities are the consequences of neuronal damage. Using ESC derived glial progenitor cells (GPC) Goldman and his group showed that Huntington GPC display a marked downregulation of transcription factors involved in oligodendroglial differentiation and accordingly transplantation of Huntington GPC resulted in less myelination in shiverer mice compared to nonaffected GPC (Osipovitch et al, ). Furthermore, overexpression of transcription factors promoting oligodendroglial differentiation (SOX10, MYRF) rescued this phenotype.…”
Section: Stem Cell Derived Oligodendrocytes For Disease Modelingmentioning
confidence: 99%
“…The higher expression of defense response genes by human astrocytes could be due to either intrinsic properties or differences in external factors such as other neuronal or glial cell types, systemic or environmental differences between human and mouse samples. To assess whether mouse and human astrocytes are different when exposed to equivalent external environments, we transplanted human astrocytes into a xenograft mouse model and compared them with the neighboring host mouse astrocytes (Benraiss et al, 2016;Han et al, 2013;Osipovitch et al, 2019;Windrem et al, 2008Windrem et al, , 2014Zhang and Barres, 2013). We purified primary human fetal astrocytes, injected them into the brains of neonatal mice (Figure 2A).…”
Section: The Human-specific Astrocyte Gene Signature Is Intrinsicallymentioning
confidence: 99%
“…We transplanted human astrocytes into host mouse brains according to published protocols (Benraiss et al, 2016;Han et al, 2013;Osipovitch et al, 2019;Wang et al, 2013;Windrem et al, 2008Windrem et al, , 2014Windrem et al, , 2017. Briefly, we purified human astrocytes as described above under the "Serum-selection purification of astrocytes" section.…”
Section: Transplantation Of Human Astrocytes Into Host Mouse Brainsmentioning
confidence: 99%
“…In this regard, recent studies have supported the readiness with which axons can remyelinate after either congenital or focal adult demyelination, if provided myelinogenic cells (Buchet et al, 2011;Duncan et al, 2009;Ehrlich et al, 2017;Piao et al, 2015;Windrem et al, 2008). In that regard, recent reports have highlighted the cell-intrinsic loss of myelination competence as the basis for remyelination failure in disorders as diverse as progressive multiple sclerosis (Nicaise et al, 2017;Nicaise et al, 2019) and Huntington disease (Ferrari Bardile et al, 2019;Osipovitch et al, 2019), suggesting that the introduction of new, myelination-competent glial progenitors might be sufficient to achieve remyelination in those cases. On that basis, we asked here if human GPCs delivered directly into the adult brain could remyelinate axons in the setting of diffuse demyelination, as might be encountered clinically in multiple sclerosis and other causes of multicentric adult demyelination.…”
mentioning
confidence: 95%